2019
DOI: 10.1016/j.jhepr.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Liver steatosis is a strong predictor of mortality and cancer in chronic hepatitis B regardless of viral load

Abstract: Highlights• HBV viral load is an important predictor of adverse outcomes in patients with chronic HBV (CHB).• Liver steatosis may co-occur with CHB but its effect on all-cause mortality and cancer has not been determined.• Liver steatosis is significantly associated with allcause mortality and cancer in patients with CHB.• The effect of liver steatosis on mortality and cancer is stronger than the effect of HBV viral load.• Patients with CHB and liver steatosis should be closely monitored, irrespective of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 37 publications
(31 reference statements)
1
79
1
Order By: Relevance
“…Our study noted significance for histological determinants of NASH such as ballooning and inflammation, but not steatosis, for clinical events in the overall cohort. In contrast, a recent retrospective study from the Middle East showed that concomitant steatosis predicts mortality and cancer in CHB patients, even when adjusted for other major metabolic factors . However, steatosis was diagnosed predominantly by ultrasound, and their multivariable analysis included covariates such as FIB‐4 and aspartate aminotransferase‐to‐platelet ratio index as surrogates for fibrosis but not AF and steatohepatitis on biopsy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our study noted significance for histological determinants of NASH such as ballooning and inflammation, but not steatosis, for clinical events in the overall cohort. In contrast, a recent retrospective study from the Middle East showed that concomitant steatosis predicts mortality and cancer in CHB patients, even when adjusted for other major metabolic factors . However, steatosis was diagnosed predominantly by ultrasound, and their multivariable analysis included covariates such as FIB‐4 and aspartate aminotransferase‐to‐platelet ratio index as surrogates for fibrosis but not AF and steatohepatitis on biopsy.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, a recent retrospective study from the Middle East showed that concomitant steatosis predicts mortality and cancer in CHB patients, even when adjusted for other major metabolic factors. (37) However, steatosis was diagnosed predominantly by ultrasound, and their multivariable analysis included covariates such as FIB-4 and aspartate aminotransferase-toplatelet ratio index as surrogates for fibrosis but not AF and steatohepatitis on biopsy. Despite differences in patient demographics, disease severity, increased HCC, and assessment of NASH as a comorbid disease state in CHB, our findings are otherwise consistent with NAFLD studies which identified AF as being the strongest predictor of clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…According to a retrospective cohort study among 270 patients with CHB, biopsy‐proven liver steatosis was established as an independent risk factor (HR = 7.27) for HCC in patients with CHB following multivariable Cox analysis . Similarly, another retrospective cohort study in 524 treatment‐naïve patients with CHB showed that liver steatosis was associated with a significantly increased risk of both all‐cause mortality and cancer (HR = 4.35), which was even stronger than the risk from HBV viral load (HR = 1.65) . We hope that more large‐scale prospective cohorts will be conducted to further establish the aggravated risk of fibrosis and HCC under concomitant NAFLD and CHB, and that more details of NAFLD‐CHB‐related HCC, such as the its histological characteristics and molecular pattern, would be explored in the future.…”
Section: Augmented Risk Of Fibrosis Cirrhosis and Hcc In Nafld And Cmentioning
confidence: 99%
“…14 Similarly, another retrospective cohort study in 524 treatment-naïve patients with CHB showed that liver steatosis was associated with a significantly increased risk of both all-cause mortality and cancer (HR = 4.35), which was even stronger than the risk from HBV viral load (HR = 1.65). 16 We hope that more large-scale prospective cohorts will be conducted to further establish the aggra- 120 both ethical issues and tremendous cost render their utility in this field nearly unrealistic. Here, we summarize new animal models that possess potential utility towards exploring the interaction between NAFLD and CHB.…”
Section: Aug Mented Ris K Of Fib Ros Is Cirrhos Is and H CC In Namentioning
confidence: 99%
See 1 more Smart Citation